Pengaruh Edukasi Gizi Melalui Bampi App Terhadap Pengetahuan, Sikap, dan Keterampilan Ibu Bayi Dalam Pemberian MP-ASI di Desa Tumbang Samba Kecamatan Katingan Tengah: Implementasi Penggunaan BampiApp dalam Upaya Meningkatkan Pengetahuan, Sikap, dan Keterampilan Ibu dalam Pemberian MP-ASI - Sugiyanto Sugiyanto; Cindra Ainie Tsabitha; Normila Normila (Universitas Airlangga, 2023)
Background: When a baby turns six months old, breast milk will no longer be able to meet their nutritional needs during the growth phase. The age range of 6 to 10 months is an important and sensitive phase of growth and development. Therefore, it is necessary to provide complementary foods according to the age stage. Efforts that need to be made include conducting health education activities that promote healthy living behaviors, one of which is nutrition education using BampiApp. Objectives: This study analyzed the difference before and after nutrition education using BampiApp on knowledge, attitudes, and skills related to complementary feeding in Tumbang Samba Village, Katingan Tengah Sub-district, Central Kalimantan. Methods: This study was a quasi-experiment with a one-group pretest-posttest design. The sample in this study consisted of 33 mothers with babies aged 6-10 months at Tumbang Samba Village, Katingan Tengah Sub-District, Central Kalimantan, chosen by purposive sampling method. Education was conducted through verbal communication to provide explanations to research respondents using BampiApp, which contains information related to complementary feeding. BampiApp was accessed online, and respondents were given one week to comprehend the material presented within the application. Data were analyzed using McNemar’s test to determine differences before and after treatment. Results: The result showed a significant increase in knowledge, attitudes, and skills in providing complementary feeding to babies in the intervention group (p<0.05). Conclusions: BampiApp can be an alternative media for the government and health workers in providing education to increase mothers’ knowledge, attitudes, and skills about complementary feeding.